Semi-rational design of an aromatic dioxygenase by substrate tunnel redirection - Jiawei Wang; Xingyu Ouyang; Shiyu Meng; Jiayi Li; Liangxu Liu; Chaofeng Li; Hengrun Li; Haotian Zheng; Chao Liao; Yi-Lei Zhao; Jun Ni (iScience)
Summary: Lignin valorization is crucial for achieving economic and sustainable biorefinery processes. However, the enzyme substrate preferences involved in lignin degradation remain poorly understood, and low activity toward specific substrates presents a significant challenge to the efficient utilization of lignin. In this study, we investigated the substrate promiscuity of ThAdo, a key enzyme involved in lignin valorization. Pre-reaction state analysis revealed that a hydrogen bond network is critical in determining substrate selectivity. By performing targeted saturation mutagenesis on residues surrounding the substrate tunnels, we identified the Y205W and Y205Q mutants, which demonstrated 0.73-fold and 0.72-fold enhancements in activity, respectively. Structural analysis indicated that the redirection of the original substrate tunnel may be responsible for the improved activity. Our study provides essential insights into the substrate preference mechanisms of lignin degrading enzymes and suggests that this tunnel-redirection strategy can be extended to other promiscuous enzymes.